Development of iBeacon application 1 - Jin, Han (Nanyang Technological University, 2022)
With the rapid advancement of technology and an increasingly interconnected world, more tools are being developed that enable people to learn useful skills and knowledge beyond what is traditionally taught in classrooms. This is also known as “informal learning”, which has in turn helped promote a culture of lifelong learning in an era of rapid skill obsolescence. Examples of “informal learning” include viewing educational YouTube videos, gamification as well as experiential learning. One popular tool used in experiential learning is museum exhibits, which provides visitors with opportunities to engage in self-directed learning. There are numerous ways technology have enhanced learning through museum exhibits – such as by making it more interactive and engaging. Examples include using iBeacons, or Bluetooth Low Energy (BLE), and an accompanying mobile application, to provide location-based content for visitors to experience. Successful iBeacons systems have already been implemented in London’s Victoria and Albert Museum and Singapore’s National Gallery. This project focuses on building an iBeacon system and creating a mobile application that will enhance the learning of users participating in experiential learning activities. However, this project will focus on outdoor learning environments, instead of the usual indoor environments that current iBeacon systems are already deployed in. The environment chosen is Yunnan Garden, due to its wealth of flora information, as well as the convenience of its location. iBeacons were configured and set up on the plaques of the plants in Yunnan Garden’s Phytoremediation Trail 2. An accompanying Android application was developed that will navigate the user along the trail and push content about the exhibits to the users.